Spiritual and moral value orientations as a guarantee of personally significant qualities of student youth - Kostyria, Iryna; Filipenko, Larysa (Національний технічний університет "Харківський політехнічний інститут", 2021)
In the article it is studied out that the spiritual and moral value orientations education of students is becoming increasingly important. It is determined that the need to establish in education approaches that ensure a harmonious balance of moral and professional qualities of graduates of higher education institutions is emphasized in the strategic documents of education of Ukraine. The research emphasizes that the effectiveness of spiritual and moral education of future engineers is realized due to students' awareness of the essence of spiritual and moral value orientations, as well as stimulating the need for professional self-development of future professionals. The article describes the implementation of the author's special course “Spiritual and moral value orientations: ways of education” in the educational process of Kharkiv National Automobile and Road University.

В статті з’ясовано, що виховання духовних моральних ціннісних орієнтацій у студентів набуває актуальності. Визначено, що потреба утвердження в освіті підходів, які забезпечують гармонійний баланс моральних і професійних якостей випускників закладів вищої освіти, акцентується у стратегічних документах освіти України щодо ціннісних орієнтирів сучасної школи та національно-патріотичного виховання в закладах освіти. В дослідженні підкреслено, що ефективність виховання духовності та моральності у майбутніх інженерів відбувається за рахунок усвідомлення студентами сутності духовних моральних ціннісних орієнтацій, а також стимулювання потреби професійного саморозвитку у майбутніх фахівців. У статті описано реалізацію авторського спецкурсу “Духовні і моральні ціннісні орієнтації: шляхи виховання” в освітньому процесі Харківського національного автомобільно-дорожнього університету.
Духовні і моральні ціннісні орієнтації як гарантія особистісно значущих якостей студентської молоді
Keywords: higher technical education institutions; future engineers; innovative forms of education; innovative methods of education; заклади вищої технічної освіти; майбутні інженери; інноваційні форми виховання; інноваційні методи виховання